PENGARUH SELF EFFICACY DAN COPING STRESS TERHADAP PSYCHOLOGICAL WELL-BEING PADA GURU ANAK BERKEBUTUHAN KHUSUS - Maylinda Triega Assyva; Magdalena Hanoum (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2022)
This study aims to determine the self-efficacy of ABK teachers, to determine the stress coping of ABK teachers, to determine the psychological well-being of ABK teachers, to find out whether there is a relationship and influence of self-efficacy with coping with stress on Psychological well- being in ABK teachers. This research is a quantitative research with correlational method. The sample used was 52 teachers of special schools at SLB Negeri Bekasi Jaya. Sampling using non- probability sampling technique. Data analysis with Spearman rank correlation and multiple regression test with a significance level of p <0.05. The results showed a good relationship between psychological well-being and self-efficacy with r = 0.353 and p value 0.010 (p 0.05), as well as a positive relationship between psychological well-being and coping with stress with r = 0.347 and ap value 0.012 (p 0.05). Furthermore, the results of data analysis using multiple regression test resulted in a coefficient of determination (R2) of 0.228 and a p value of 0.001 (P 0.05).